1961
DOI: 10.2307/2985206
|View full text |Cite
|
Sign up to set email alerts
|

The Variable Lot-Size Acceptance Sampling Plan for Continuous Production

Abstract: In this article previously published acceptance sampling plans for continuous production are summarised and certain shortcomings pointed out. A new procedure is put forward in the Variable Lot‐Size Acceptance Sampling Plan, which combines the useful features of lot‐by‐lot plans with the flexibility of continuous plans. The advantages and general features of this plan are described, and a table is given which enables AOQL values to be calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In this paper, we have proposed the problem of minimizing the ATI of Read & Beattie's (1961) variable lot-size sampling plan for continuous production. From the above analysis, we conclude that the short-run CSP-1 plan has the smallest average inspection unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we have proposed the problem of minimizing the ATI of Read & Beattie's (1961) variable lot-size sampling plan for continuous production. From the above analysis, we conclude that the short-run CSP-1 plan has the smallest average inspection unit.…”
Section: Discussionmentioning
confidence: 99%
“…Read & Beattie (1961, p. 153) showed that the average total inspection (ATI) is less for the variable lot-size plan than for the equivalent fixed lot-size plan having the same values of lot size (N), sample size (n), and acceptance number (c). Kalyanasundaram & Balamurali (2000) further presented the design of Read & Beattie's (1961) plan indexed by the acceptable quality (AQL) and average outgoing quality limit (AOQL). In this paper, we propose the problem of minimizing the ATI of Read & Beattie's (1961) variable lot-size sampling plan for continuous production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, an attempt will be to match, n(p), the long run proportion of product which is accepted, about two target quality specifications, p=po and p =p,. It should be noted that n(p) is similar to the Type C OC curve defined by Read and Beattie (1961) .5b, an expression which describes conditions for the equivalence qf the average fraction inspected may be given as follows:…”
Section: Comparing Performance Of Ssp Vs Cspmentioning
confidence: 99%
“…If the sample contains c or fewer underweights, the batch is accepted; otherwise it is rejected and put aside, with an identification label, for sorting. This method of 'variable batch size' sampling was first introduced by Reed and Beattie (1961).…”
Section: Steel Productionmentioning
confidence: 99%